INOVASI PENGOLAHAN PANGAN LOKAL: PENINGKATAN NILAI EKONOMI UBI JALAR KUNING DAN SAWI HIJAU DI DESA KESIMAN, TRAWAS - Rukmini, Rukmini; Nuraziza, Siti Shela; Alamsyah, Bahrul; Ahmada, Dzikrilla Al; Sidqiyah, Nasfa Laura; Akbar, Mohammad Aziz; Romadhoni, Muhammad Rizqi; Khodijah, Siti; Tsabita, Nur Afina; Qulub, Mohammad Tathmainul; Ramadhan, Noviandri Dwiprama; Attohiri, Rifqon Hadi; Makhrus, Subekhan Mu'Min; Geovanni, Muhammad Anand; Sujana, Munding Dharma; Junaihil, Junaihil; Umroh, Dwiyah Fakhriatul; Tias, Leli Dwi Agustining; Kuswoyo, Nyoko Adi (Universitas Padjadjaran, 2025)
Kesiman Village, located in Trawas District, Mojokerto Regency, has significant agricultural potential, particularly in yellow sweet potatoes and green mustard greens. However, these agricultural products have not been optimally utilized, as most of the community sells them in fresh form without processing to increase their added value. This situation results in low selling prices and limited shelf life, preventing the local economy from fully developing. To address this issue, it is essential to enhance the community's knowledge and skills in processing local agricultural products into value-added goods, which can boost competitiveness and extend the shelf life of these products. This community service activity involved 24 participants, including Small and Medium Enterprises (SME) operators and residents of Kesiman Village. Through a workshop titled